Evaluation of oral stereognosis in completely edentulous patients with palatal tori - Indumathi Sivakumar; Rachel Chua Hui Shien; Nur Lyanna Mahfuzah Binti Mohamad Johar; Sham Wern Xuan; Sin Pi Xian (Journal of Oral Research, 2021)
Background: The corollary is not investigated in the completely edentulous patients with palatal tori. Objective: The aim of this study was to assess the oral stereognostic ability in completely edentulous patients with palatal tori. Material and Methods: Thirty-four completely edentulous patients aged 50 to 89 years were allocated to Group 1 (without palatal tori, n=18) and Group 2 (with palatal tori, n=16). The oral stereognostic test was conducted using 6 intraoral test pieces (circle/square/rectangle/triangle/plus/toroid) that were fabricated to standard dimensions using the light cure acrylic resin. Each test piece was placed in the patient’s mouth and was asked to manipulate the test piece between the tongue and the palate. The patients identified the shapes by matching them on a shape chart. Each correct identification was assigned a score of 1. The response time taken to identify each shape was recorded. Statistical computation was done using a chi - square test and Mann-Whitney U test. Results: Significant difference was observed in the overall scoring percentages between the 2 groups (p<0.05). Group 2 had lower oral stereognostic scores compared to group 1 (p<0.05). There was no statistically significant difference in the mean response time for identifying the shapes among the groups, however group 2 patients had longer response time. Conclusion: Oral stereognostic ability of the completely edentulous patients with torus palatinus was lower when compared to completely edentulous patients without tori.